Does the relationship between IgE and the CD14 gene depend on ethnicity? - Zhang, Guicheng; Goldblatt, J.; LeSouëf, P. (2008)
This review considers the data from studies analysing associations between the CD14C-159T single nucleotide polymorphism (SNP) and asthmatic phenotypes and discusses the variability of the conclusions. By searching PubMed and EMBASE for articles on CD14C-159T -related population or family-based association studies, 47 were identified up till September 2007. Collectively, the studies reviewed herein consistently showed population differences in frequencies of the alleles of the SNP, with African descent having the highest C allele frequencies, followed by Caucasians and Asians. The T allele of the SNP was associated with increased sCD14 in some studies but not in others. Inconsistently, the C allele, or even occasionally the T allele, was associated with atopic phenotypes in a population subgroup. There are several explanations for these inconsistencies, including lack of power, linkage disequilibrium, gene-gene interactions, population admixture and gene-environment interactions. If the SNP was associated with functional changes to the coded protein and thus modulating susceptibility to allergic disease, its effect may be modest and dependent on other co-existent, ethnicity-specific, genetic or environmental risk factors. © 2008 The Authors.